用高附加值技术改造中国传统产业 = Transforming traditional industries in China with the high value-added technologies - 王瑞林 Wang, Ruilin (2008)
The thesis analyses the classification of China’s industries based on the theories of industrial economics. The study focuses on the impacts of traditional industries on the national economy. With China’s admission into WTO, the traditional industries faces even more competitions from both domestic as well as international markets than before.